Intramedullary nailing of paediatric tibial fractures. Comparison between flexible and rigid nails - Widbom-Kolhanen, Sara (My University, 2019)
The purpose of this study was to compare flexible and rigid intramedullary nailing of tibial fractures in patients under 16 years. Flexible intramedullary nailing is widely used and preferred fixation method when operative management is required. However, the lack of rigidity is associated with possible complications including axis deviation, delayed union and malunion. Rigid intramedullary nail provides better control of fracture alignment, but it has been generally contraindicated in paediatric population except at the end of the growth period because of concerns about growth disturbance. This was a retrospective study of 56 patients under 16 years with a tibial diaphyseal fracture who were treated with intramedullary nailing at Turku University Hospital during 2008-2017. Twenty-six patients were treated with a flexible intramedullary nail and 30 patients with a rigid nail. The patient charts and radiographs were evaluated to identify demographic characteristics and several variables were measured preoperatively, as well as six to 12 weeks postoperatively in addition to final follow-up radiographs. Based on the results of this study rigid intramedullary nailing can be recommended for children over 13 years for the treatment of tibial fractures in need of surgical stabilisation as rigid nailing allows more precise fracture alignment without increased risk of growth disturbance.
Keywords: tibial fracture, ESIN, flexible intramedullary nail, rigid intramedullary nail